(untitled) (Palíndromo, 2022)
In the first months of the pandemic, in 2020, I painted watercolours while repeatedly observing the meeting of water and rock in the sea. This theme emerged as a dialogue that brought me the realization, with a start, of this chance encounter that made me connect with this meeting of forces. Excerpts from a diary from these same months became drawings that seek to bring the distant view of the sea and the glitter in the waters, in silver nankeen on parchment paper. This series is constituted by encounters that also occur with the video Sea Lion and with a small object left by the sea on the sand, which was registered in photography.